FORMULATION OF HAND SANITIZER GEL PREPARATION COMBINATION OF NEMBA LEAF (AZADIRACHTAINDICAA.JUSS) ETHANOL EXTRACT OF AND EXTRACT OF ALOE VERA (ALOE VERA)AGAINS STAPYLOCOCCUCAUREUS BACTERIA - Sari, Rika Puspita; Harnis, Zola Efa Harnis; Nina Irmayanti Harahap; Rissa Dewi Ramadhani (Jurnal EduHealth, 2022)
The use of hand antiseptics in the form of gel preparations which are more popular with the namepreparations hand sanitizer usually contain antiseptics in the form of synthetic chemicals which are relatively expensive and often cause skin health problems, such as dry skin. The leaves of the neem plant and aloe vera gel have been shown to be able to treat several diseases, one of which is being able to be a companion drug for antibacterial treatment. The method used in this research is experimental method because it is intended to determine the effect or relationship between the independent variables called treatment factors, namely thegel formulation Hand Sanitizer from a combination of neem leaves and aloe vera gel with concentrations of 5%, 10%, and 15%, with the dependent variable called the observation factor, namely the test. Organoleptic, pH, homogeneity, dispersion test, irritation test and antibacterial activity tes. The results obtained from this study are that neem leaf ethanol extract and aloe vera gel can be formulated intopreparations hand sanitizer gelwith concentrations of 5%, 10% and 15%, with homogeneous preparations, pH around 6.68-7.03, with dispersion ranges from 4.4cm - 5.5 cm, and stable at 4 weeks of storage.. Results preparations hand sanitizers containing ethanol extract of neem leaves 15% provides a strong barrier against Staphylococcus aureus was 13.80 ± 0.29 mm.